(untitled) (Research, Society and Development, 2020)
This study aimed to present a brief history of the disease and its potential risk of transmission after eradication of the vector in a blood bank, as well as to address proposals for monitoring and prevention in blood banks to prevent the spread of the disease. It is a narrative review of the literature with manuals, books, theses, monographs and scientific journals published in Portuguese and English, in the open and virtual libraries of BIREME (Regional Library of Medicine), LILACS (Latin American Literature in Health Sciences) and SCIELO (Scientific Electronic Library Online) using the descriptors: trypanosomiasis, Chagas disease and hemotherapy. Across Latin America, the incidence rate of Chagas disease was 6.8% in the 1980s and decreased to 1.3% in 2006, which represents a significant change in the epidemiological profile. Both in Brazil and in other countries, hemotherapy services have been adopting new technologies to minimize the spread of infectious agents during transfusion.